The effect of 48-weeks azithromycin therapy on levels of soluble biomarkers associated with HIV-associated chronic lung disease - Hameiri-Bowen, Dan; Yindom, Louis-Marie; Sovershaeva, Evgeniya; Bandason, Tsitsi; Mayini, Justin; M Rehman, Andrea; Simms, Victoria; Gift Ngwira, Lucky; Flagestad, Trond; Jarl Gutteberg, Tore; McHugh, Grace; Abbas Ferrand, Rashida; et al. (International immunopharmacology, 2023)
[Display omitted] •Azithromycin treatment reduced plasma levels of CRP, E-Selectin and MMP-10 in children with HIV-associated chronic lung disease.•Limited immunomodulatory properties observed in large panel of soluble markers.•No treatment effects were sustained after cessation of treatment. HIV-associated immune activation contributes to chronic lung disease (CLD) in children and adolescents living with HIV. Azithromycin has immunomodulatory and anti-microbial properties that may be useful for treating HIV-associated CLD (HCLD). This study describes the effect of azithromycin on expression of plasma soluble biomarkers in children and adolescents with HCLD. This study was nested within a multi-site double-blind, placebo controlled, randomised controlled trial (RCT) of azithromycin in individuals aged 6–19 years with HCLD (defined as FEV1 z-score < -1) in Malawi and Zimbabwe (BREATHE (NCT02426112)). Participants were randomized 1:1 to once-weekly oral azithromycin with weight-based dosing, for 48 weeks, or placebo. Twenty-six plasma soluble biomarkers were measured on a MagPix Luminex instrument at enrolment, after 48-weeks of treatment and 24-weeks after treatment cessation. Mixed effects models were constructed to compare biomarker expression across treatment and placebo groups. Weekly azithromycin was associated with reduced levels of C-Reactive Protein (CRP), E-Selectin, Matrix metalloproteinase 10 (MMP-10). Treatment effects for all soluble biomarkers were not sustained 24-weeks after treatment cessation with biomarker expression returning to pre-treatment levels. We observed real-world effects of azithromycin on acute inflammation, neutrophil accumulation, and extracellular matrix degradation, that were not sustained after treatment cessation. These results are pertinent when using azithromycin for its immunomodulatory properties, or targeting pathways represented by the soluble biomarkers in this study.